2006
DOI: 10.1073/pnas.0602173103
|View full text |Cite
|
Sign up to set email alerts
|

Phonological typicality influences on-line sentence comprehension

Abstract: Since Saussure, the relationship between the sound and the meaning of words has been regarded as largely arbitrary. Here, however, we show that a probabilistic relationship exists between the sound of a word and its lexical category. Corpus analyses of nouns and verbs indicate that the phonological properties of the individual words in these two lexical categories form relatively separate and coherent clusters, with some nouns sounding more typical of the noun category than others and likewise for verbs. Addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
221
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 160 publications
(230 citation statements)
references
References 40 publications
(37 reference statements)
5
221
3
Order By: Relevance
“…For example, one concern about experiments of this type is the difficulty of fully disentangling a sentence's high level properties (e.g., its meaning) from its low level properties (e.g., its shape and form, c.f., Farmer, Christiansen, & Monaghan, 2006). While Sklar and colleagues made efforts to rule out lower level explanations of their results, doing so is difficult because sentences with different meanings necessarily have different forms.…”
mentioning
confidence: 99%
“…For example, one concern about experiments of this type is the difficulty of fully disentangling a sentence's high level properties (e.g., its meaning) from its low level properties (e.g., its shape and form, c.f., Farmer, Christiansen, & Monaghan, 2006). While Sklar and colleagues made efforts to rule out lower level explanations of their results, doing so is difficult because sentences with different meanings necessarily have different forms.…”
mentioning
confidence: 99%
“…This systematicity is likely to be advantageous because it provides information about the general category of the word, rather than at the level of the individual word [43,58]. For mapping from form onto such category levels, systematicity in the spoken word is beneficial [21,59], but for the more specific task of individuating words' meanings, arbitrariness is advantageous, at least for larger vocabularies [13]. For both categorization and individuation, division of labour within the structure of the word may be beneficial [13,27,60].…”
Section: Discussionmentioning
confidence: 99%
“…Systematicity refers to broad statistical relationships among groups of words belonging to the same semantic or syntactic categories. For instance, Farmer, Christiansen, and Monaghan (2006) showed that English nouns tend to be more phonologically similar to other nouns than to verbs (and vice versa for verbs). Similarly, Reilly and Kean (2007) demonstrated that there are general differences in the forms of concrete and abstract English nouns.…”
Section: Arbitrariness and Nonarbitrarinessmentioning
confidence: 99%